The lure of ice-templating: Recent trends and opportunities for porous materials. (1st April 2018) - Deville, Sylvain
Abstract: Ice-templating is a simple materials processing and shaping route where the growth of crystals from a solvent template the porosity. Although the principles of ice-templating were established a long time ago, it has lured considerable attention over the past 5 years to become a well-established processing route for porous materials of all kinds. In this viewpoint, I summarize the current status and recent trends of ice-templating studies. I then review the unique assets of ice-templating and propose a roadmap of the most promising or pressing questions and opportunities in this domain. Graphical Abstract: